Diagnostic performance of a radiological Fagotti score assessed on diffusion-weighted magnetic resonance imaging for predicting tumor resectability in ovarian cancer patients: a feasibility study - Siegenthaler, Franziska; Zurbriggen, Selma; Wyss, Corinne; Imboden, Sara; Saner, Flurina; Wampfler, Julian; Christe, Lucine; Solass, Wiebke; Hofer, Seline; Christe, Andreas; Heverhagen, Johannes T.; Mueller, Michael D.; et al. (Frontiers in Oncology, 2025)
ObjectiveIn ovarian cancer, the correct selection of patients for cytoreductive surgery is of great importance. The aim of this study was to evaluate the diagnostic performance of the Fagotti score assessed on preoperative diffusion-weighted magnetic resonance imaging (DW-MRI) for predicting tumor resectability in patients with ovarian cancer.MethodsThis retrospective cohort study included patients with ovarian cancer who underwent surgical treatment between 2014 and 2022 at University Hospital Bern, Switzerland. All patients had a preoperative MRI performed. The surgical and MRI Fagotti scores were assessed retrospectively, and follow-up data were available through standardized databases and follow-up controls.ResultsA total of 52 imaging studies in 50 patients met the inclusion criteria. The majority of the patients presented with primary diagnosis (73.1%), serous histological subtype (75.0%), and advanced International Federation of Gynecology and Obstetrics (FIGO) stage (76.9%). The mean surgical Fagotti score was 3.4 (±3.24), while the mean MRI Fagotti score was 2.8 (±2.92). Consistency between the surgical and MRI assessments was 94.2% for stomach infiltration, 80.8% for superficial liver metastasis, and 80.8% for peritoneal, 80.8% for mesenteric, 78.8% for small bowel, 75.0% for omental, and 65.4% for diaphragmatic involvement. An MRI Fagotti score of <8 predicted a no residual disease (R0) resection with a sensitivity of 97.4%, a positive predictive value of 86.0%, and a negative predictive value of 83.3%. Patients with an MRI Fagotti score of <6 showed a significantly longer recurrence-free survival (log-rank, p = 0.020) and overall survival (log-rank, p = 0.043) compared to patients with an MRI Fagotti score of 6 or higher.ConclusionAccording to the study results, the assessment of the Fagotti score on preoperative imaging with DW-MRI is feasible and useful in predicting tumor resectability in patients with ovarian cancer. Furthermore, an MRI Fagotti score higher than 6 is associated with worse oncological outcomes. However, further studies on a larger patient population are needed to confirm our results.